The one with no-one: Oral health and quality of life among rohingya refugee: A cross-sectional study - Lav Kumar Niraj; Ashish Singla; Ritu Gupta; Basavaraj Patthi; Kuldeep Dhama; Irfan Ali (Wolters Kluwer Medknow Publications, 2017)
Introduction: Rohingyas are considered to be one of the largest population who has immigrated in India throughout the past. The needs and health status of the immigrants are vital due to their input to the health of the country. The oral health professional confronts many challenges in treating them due to their different cultures. Aim: The aim is to assess the oral health status and oral health-related quality of life among Rohingya refugees staying in refugee camps in New Delhi India. Materials and Methods: Out of the total 212 people, 201 (94.81%) people agreed to be the part of the study who are residing in the refugee camp. Assessment of the oral health status and oral health-related quality of life was peformed in accordance with criteria laid down by the WHO in oral health assessment survey basic methods, 2013 and oral health impact Profile-14. The data were statistically analyzed using descriptive statistics such as mean, standard deviation, and percentage and Spearman's rank correlation coefficient test. The level of significance was set at 5%. Results: Caries prevalence was found to be 83.92% among adults aged 15 years and above. Periodontal disease with gingival bleeding was present among the entire study population. Caries prevalence was found to be 85.23% among children below 15 years. A decayed tooth, missing tooth, decayed missing filled tooth was found to be highly, significantly correlated with the functional limitation, physical pain, psychological discomfort. Conclusion: The most common dental problems were gingival or periodontal problems, dental caries, and decayed teeth due to the high level of unmet needs in the study population which highlights the need for a comprehensive dental care program. Further, research has to be conducted on the oral health of refugees living in developing countries like India and treatment camps are of the urgent need to provide the dental services.